Perancangan Model Kompetensi Behaviour Berbasiskan Job Competency Assessment (JCA): Studi Kasus Perusahaan Otobus - Dodi Permadi; Suci Fika Widyana; Noneng Nurjanah; Jaka Maulana; Dera Thorfiani; Ade Pipit Fatmawati; Ali Mohamad Rezza (Jurnal Locus Penelitian dan Pengabdian, 2026)
Organizational transformation in the era of digital competition requires strategic human resource management, specifically through the development of measurable and relevant competencies. This study aims to design a Behavioral Competency Model for a public transportation provider based on Job Competency Assessment (JCA), utilizing a Design Science Research (DSR) approach. The research employed a qualitative methodology involving document and content analysis, thematic coding, and conceptual mapping of the 2025 HR Competency Dictionary, supplemented by a comprehensive literature review. The results yielded a layered behavioral competency model consisting of core, general, leadership, and functional competencies, structured into a four-level hierarchy: basic, intermediate, advanced, and strategic. This model effectively integrates work behavior and organizational performance while fostering a culture of safety, public service, and integrity. The findings demonstrate that behavioral competencies are not merely individual attributes but strategic mechanisms linking individual performance to organizational excellence and successful institutional transformation. The primary contribution of this research is the development of an evidence-based behavioral competency model that aligns JCA principles with the strategic needs of the public transportation sector. Furthermore, it enriches competency management literature with a conceptual framework adaptable to the challenges of operational safety, public service, and digital transformation.